Implementasi Social Enviromental Governance (ESG) pada Sustainable Financing Perspektif Maqashid Syariah (Studi pada Bank Syariah) - Sulistyowati, Sulistyowati; Anam, Choiril (Universitas Islam Raden Rahmat, 2025)
To improve the services Islamic banking institutions in their operational activities, especially providing sustainable financing to environmentally friendly customers by implementing Environmental Social Governance, the research to conducted is field research and documentary to answer questions chronologically and systematically about the implementation of Environmental Social Governance (ESG) sustainable financing intensively and comprehensively reviewing the review of the maqashid sharia of Asy-Syathibi's thoughts. The results of research maximized to achieve the research objectives, including to contribute to thinking and development of science for the academic community of universities in general and especially academic community of IAIN Kediri in Islamic banking and development review the perspective of maqashid sharia related environmental social governance in sustainable financing, while increasing the insight and discourse of all parties related to Islamic banking in terms of funding or financing that implements ESG not to pursue profit alone, but also to pay attention the benefits for the environment, society, and government, and especially input for Islamic banking institutions to always implement environmental social governance in operational activities.